Supporting bereavement and complicated grief in primary care: a realist review - Pearce, C; Wong, G; Kuhn, I; Barclay, S (Royal College of General Practitioners, 2021)
Background Bereavement can have significant impacts on physical and mental health, and a minority of people experience complicated and prolonged grief responses. Primary care is ideally situated to offer bereavement care, yet UK provision remains variable and practitioners feel uncertain how best to support bereaved patients.